FINANCIAL STATEMENT FRAUD: EVIDENCE FOOD AND BEVERAGE COMPANIES - Arnindhita , Rietra Aryza; Abidin, Fitiyan Izzah Noor; Hariyanto , Wiwit; Biduri , Sarwenda (PT. Antis International Publisher, 2024)
This research aims to analyze the influence of Fraud Diamond, Financial Leverage, and Financial Stability on Fraudulent Financial Statements. This research uses quantitative methods with company annual financial report data that has been published during the 2017-2021 period and can be accessed via the official website of the Indonesia Stock Exchange at www.idc.co.id. The population chosen as the research object in this study is manufacturing companies in the food and beverage industry subsector listed on the Indonesia Stock Exchange (BEI) in 2017-2021. The sample selection technique in this study used a purposive sampling technique. In accordance with the research results, it was found: The results of the analysis of the influence of Fraud Diamond have a significant effect on the Fraudulent Financial Report, Financial Leverage has a significant effect on the Fraudulent Financial Report, and Financial Stability has no effect on Fraudulent. financial statements. It can be concluded as follows